Analysis of the Influence of the US-China Trade War on the Indonesian Economy and the Potential of Sharia Investment as a Solution - Rizki Dwi Putra Rosadi; Wildan Jauhari; S Suratno (Suhuf)
The trade war between the United States and China that began in 2018 significantly impacted the global economy, including Indonesia. The tariff policy implemented by the U.S., especially the one that will continue at its peak in 2025, causes global economic uncertainty, disrupts international supply chains, and lowers Indonesia's trade with the two countries. This study aims to analyze the role of sharia investment in reducing the impact of protectionist policies implemented by the U.S. and China on the Indonesian economy. Using a descriptive qualitative approach with thematic analysis methods and a systematic literature review, this study identifies that Sharia investment can strengthen Indonesia's economic resilience, especially by diversifying funding sources to real sectors such as infrastructure and renewable energy. The findings suggest that sharia investment, with the principles of prudence and sustainability, can be an alternative solution that reduces dependence on volatile global markets and enhances Indonesia's economic stability amid global uncertainty.